Below‐gap emission bands in undoped GaN and its excitation density dependence. Issue 5 (9th December 2015) - Julkarnain, M.; Fukuda, T.; Kamata, N.; Arakawa, Y.
Abstract: The below‐gap emission bands of undoped GaN grown by MOCVD on sapphire substrate have been investigated by photoluminescence technique. The intensity of yellow luminescence decreases due to the saturation of deep states with increasing excitation power that reflects the contribution of deep states at actual device operating condition. The excitation induced blue‐shift of emission energy rationalizes the DAP characteristics. The integrated photoluminescence intensity of each band is analysed experimentally and theoretically by a power law model, and the reasonable agreement between experiment and model calculation justify our model consideration. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)